Method for determining the power loss in the contact system - Kuznetsov, V. G.; Bosiy, D. A.; Kiriluk, T. I. (Science and Transport Progress, 2012)
The authors offer conferencing method for determining the power loss coefficient for the contact network. Authors have received expressions for the equivalent value of loss coefficient for the existing power schemes contact network.